The drinking of a Salvia officinalis infusion improves liver antioxidant status in mice and rats - Lima, Cristóvão F. (2005)
In this study we evaluate the biosafety and bioactivity (antioxidant potential) of a traditional water infusion (tea) of common sage (Salvia officinalis L.) in vivo in mice and rats by quantification of plasma transaminase activities and liver GST and GR enzyme activities. The replacement of water by sage tea for 14 days in the diet of rodents did not affect the body weight and food consumption and did not induce liver toxicity. On the other hand, a significant increase of liver GST activity was observed in rats (24%) and mice (10%) of sage drinking groups. The antioxidant potential of sage tea drinking was also studied in vitro in a model using rat hepatocytes in primary culture. The replacement of drinking water with sage tea in the rats used as hepatocyte donors resulted in an improvement of the antioxidant status of rat hepatocytes in primary culture, namely a significant increase in GSH content and GST activity after 4 hours of culture. When these hepatocyte cultures were exposed to 0.75 or 1 mM of tert-butyl hydroperoxide for 1 hour, some protection against lipid peroxidation and GSH depletion was conferred by sage tea drinking. However, the cell death induced by t-BHP as shown by LDH leakage was not different from that observed in cultures from control animals. This study indicates that the compounds present in this sage preparation contain interesting bioactivities which improve the liver antioxidant potential.